Narratives about the past and cognitive polyphasia: Remembering the argentine conquest of the desert - Barreiro, Alicia Viviana (2016)
The Conquest of the Desert was a military campaign waged by the Argentine government against the indigenous population during the late 19th century. This period of national organization and territorial expansion involved the extermination of the native populations, with thousands being killed or sold to wealthy landowners. This article reports the findings from an ethnographic study conducted in a city founded by the military forces during this period, where nowadays descendants of the military men and the European immigrants live alongside the descendants of the original inhabitants. In observations of the symbolic resources of the city and in interviews and discussions with descendants of European and military men, we identified 2 distinct narratives about this historical process: a traditional account concerning the peaceful coexistence of colonizers and indigenous groups, and a revisionist account that emphasizes the genocide of indigenous groups and the looting of their lands by the Argentine military. We consider the juxtaposition of these 2 narratives as an expression of a state of cognitive polyphasia that allows Argentine people to espouse a "politically correct" version of the past while, at the same time, denying the conflict between colonizers and indigenous groups. We submit that this juxtaposition serves to make it possible for them to cope with the collective guilt that arises in relation to their ancestors´ behavior, while at the same time delegitimizing ongoing indigenous claims about past injustices and the need for historical reparation.